BC2P-1305: an enhanced data security in cloud computing network using blockchain based ChaCha20-Poly1305 cryptography - Golla Bala, Renuka; Gnanavel, S. (Frontiers in Blockchain, 2025)
As cloud computing becomes more prevalent, the need for robust data security to address issues related to confidentiality, integrity, and access control has grown significantly. This paper introduces BC2P-1305, a cloud security framework that combines blockchain technology with the ChaCha20-Poly1305 cryptographic algorithm. The framework utilizes ChaCha20-Poly1305 for efficient encryption and authentication, offering low latency and strong protection against cryptographic attacks. Blockchain is employed for secure, tamper-proof metadata storage and integrity checks, while smart contracts automate and enforce detailed access control policies. Additionally, a secure key management system ensures that decryption keys are provided only to authorized users. Experimental results show that BC2P-1305 outperforms current technologies such as AES-GCM and RSA (2048-bit) across several performance metrics. Encryption latency is reduced by 40% compared to AES-GCM and 75% compared to RSA, while decryption latency is 35% and 80% lower, respectively. The blockchain transaction processing time using a Proof-of-Authority consensus mechanism is 60% faster than that of Proof-of-Work systems. Furthermore, BC2P-1305 shows a 30% reduction in CPU and memory usage and a 20% improvement in throughput over AES-GCM. These findings demonstrate that BC2P-1305 is scalable, efficient, and well-suited for securing cloud data, offering a promising solution to modern cloud security challenges.